Modification of polyurethane coating based on palm oil with filler bentonite to improve heat resistant properties - Teuku Rihayat; Shafira Riskina; Adi Saputra Ismy (Politeknik Negeri Lhokseumawe, 2020)
This work aims to prepare and characterize polyurethane nanocomposite sequences modified with bentonite as fillers and palm oil as a soft segment component while Toluene Diisocyanate (TDI) was chosen as a hard segment component. Bentonite fillers are needed to provide heat resistance to the polyurethane coating. Morphological, structural and thermal polyurethane nanocomposites are characterized by SEM, FTIR, and TGA. FTIR analysis is the NH urethane group in palm oil polyurethane compounds while the absorption of C=O urethane group widens at 1735 cm-1. While the CH group occurs at absorption wavelengths of 2120-2180 cm-1, adding bentonite (7% by weight) is completely laminated and well dispersed in the form of a mixture of peeling / intercalating layers in the polymer matrix. Polyurethane nanocomposites have a morphology separated by clearer microphase. The resulting thermal stability is higher compared to the addition of bentonite 3 and 5% by weight. Because of its enhanced features, the polymer developed can be considered a material with heat resistance as a coating.